Pengetahuan dan Perilaku Swamedikasi Dispepsia di Masyarakat: Kajian Literatur - Utari, Weny Syafitri; Andanalusia, Mahacita (Wiraraja Medika : Jurnal Kesehatan, 2024)
Dyspepsia is a syndrome of the upper gastrointestinal tract that can cause symptoms such as heartburn nausea and vomiting that can interfere with the patient's activities. Dyspepsia with mild symptoms can be treated by self-medication. This literature review was conducted to describe the knowledge and behavior of dyspepsia self-medication by the community. A literature review was conducted by searching databases through Google Scholar on the knowledge and behavior of dyspepsia self-medication in the community between 2022-2023 that met the inclusion and exclusion criteria. 10 relevant articles were obtained where 6 studies stated that the community had good knowledge and behavior for dyspepsia self-medication, 2 studies showed good knowledge and poor behavior towards dyspepsia self-medication, 1 study showed a high level of community knowledge and fairly good behavior for dyspepsia self-medication however, there was no relationship between the two and 1 study that had poor knowledge but had good behavior towards dyspepsia self-medication. This indicates that good knowledge will not always be in line with good behavior, nor will good behavior always be in line with good knowledge